2015
DOI: 10.1016/j.jenvrad.2015.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Surface charge accumulation of particles containing radionuclides in open air

Abstract: Radioactivity can induce charge accumulation on radioactive particles. However, electrostatic interactions caused by radioactivity are typically neglected in transport modeling of radioactive plumes because it is assumed that ionizing radiation leads to charge neutralization. The assumption that electrostatic interactions caused by radioactivity are negligible is evaluated here by examining charge accumulation and neutralization on particles containing radionuclides in open air. A charge-balance model is emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
(88 reference statements)
0
9
0
Order By: Relevance
“…4 aerosols ranges from less than ten negative elementary charges to greater than one hundred positive charges (Gensdarmes et al, 2001;Kim et al, 2015). The amount of charge an aerosol can have depends on its particle size and surface area, with larger particles, having larger surface area, holding more charge than smaller particles (Wu et al, 2005).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…4 aerosols ranges from less than ten negative elementary charges to greater than one hundred positive charges (Gensdarmes et al, 2001;Kim et al, 2015). The amount of charge an aerosol can have depends on its particle size and surface area, with larger particles, having larger surface area, holding more charge than smaller particles (Wu et al, 2005).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The self-charging process makes radioactive aerosols unique as compared to ambient aerosols, where charge is generally assumed to be neutralized or very low (single elementary unit) due to aerosol interaction with the ions present in the air (Jayaratne et al, 2014) and charge on ambient indoor aerosols is found to be lower than charge on outdoor aerosols (J-Fatokun et al, 2008). In this study, through use of a corona charger, the aerosols were given a charge in a range representative of radioactive aerosols (Kim et al, 2015). This aerosol charge introduces an electrostatic interaction with other aerosols, and also with surfaces present in the surroundings (Filippov, 1992;Wistrom and Khachatourian, 2001).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Two or more mechanisms may operate simultaneously [30]. It has been reported that electrostatic charge generated by radioactivity contributes significantly to surface interactions between particles and environmental surfaces [31]. In assessing the potential for interactions with complexing agents, uptake into the food chain and mobilization, paradoxically the same governing variables and processes affecting heavy metals and metalloids in the biosphere can be extrapolated to analogue radionuclides [32,33].…”
Section: Sorption Mechanismsmentioning
confidence: 99%
“…Charge of the radionuclides is the determining factor for exchange sorption. It has been shown that radioactive particles can be strongly charged and yield an asymmetric bimodal charge distribution [34,35]. Therefore the processes involving electrostatic interactions will play a role in predicting their transport.…”
Section: Ion Exchange Sorptionmentioning
confidence: 99%
See 1 more Smart Citation